(untitled) (Journal of Science and Technology, 2016)
Four new derivatives ofÆ´-(4-benzhydryl-1-piperaziny)-a-phenyl propanols were prepared using Grignard’s reaction. They were isolated as solid bases and their structures, elucidated using I.R. and Hnmr spectroscopy. The compounds were screened for antispasmodic activity on guinea pig ileum, suing acetylcholine as the spasmodic agent. They all gave complete inhibition 80% maximal acetlcholine-induced contractions at microgram concentration.